Caught on camera, posted online: mediated moralities, visual politics and the case of urban 'drought-shaming'. Issue 1 (2nd January 2017) - Milbrandt, Tara
Abstract : The 'shaming' of subjects caught on camera, engaging in socially transgressive acts of varying kinds, has become a familiar occurrence and locus of ambivalent possibility in contemporary public culture. In this article, I theorise the socio-moral complexities and visual politics of ostensibly civic forms of online shaming through an in-depth analysis of a single case: urban 'drought-shaming' in California (2014–2015). Drawing on interpretive methods of social analysis and anchored by the classical sociological tradition, I highlight the role of images, especially the circulation of still photographs taken and posted by ordinary members, in the emerging problematisation of excessive water use at the centre of this case. Understood as a vital and diminishing resource within an interconnected and interdependent social order, water was made sacred; it was prohibited from being handled in mundane or carelessly reckless ways during the drought. A state-of-emergency came to be constituted (also) as a moral drama. The language and practices constitutive of drought-shaming, I argue, contributed to a popular sociological imagination of water use whose critical dimensions transcend the specificities of this case. To highlight its ritual structure within the context of a viable and organically solidaristic collective order, I compare online civic shaming with the 'status degradation ceremony', as theorised by Harold Garfinkel in the 1950s. Comparable in that it constitutes a new form of public denunciation with socially integrative and renewing possibilities, there are also differences that shed light onto some of the new and defining elements of public shaming in a digitally convergent, visually mediated, and (more) participatory media-sphere. Finally, revealing significant overlap and collaboration between social, news, and tabloid media in the social production of mediated shaming today, this study is located at the border of visual sociology and a critical sociology of visual representation in contemporary mediated society.